Improvising to reveal: the school on stage and its constituent discourses (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The work Qualquer Semelhança Não É Mera Coincidência, by Jean Carlos Gonçalves, analyzes the school as a symbolic and performative space, using theatrical improvisation as an investigative and political method. Based on Dialogic Discourse Analysis and Foucaultian studies, the research reveals how school discourses are tensioned and contested on theatrical studies. Through a dramaturgical structure and theater games, the author highlights power relations, subjectivities, and symbolic disputes in everyday school life. The work contributes to Education, Language and Art by valuing listening and testimony as legitimate forms of knowledge production.
Keywords: theatrical improvisation; dialogic analysis; school discourse; education and art; power and language